The Effect of Kuaspadu Herbal Drink (Turmeric, Tamarind, Gotu Kola, and Honey) on Menstrual Pain Reduction in Female Adolescents - Farida Umamy; Ririn Anggriani Sitorus; Febria Havina Alni (GLOBAL HEALTH SCIENCE GROUP, 2025)
Kuaspadu herbal drink, consisting of turmeric, tamarind, gotu kola, and honey, is a traditional Indonesian remedy commonly used as an alternative treatment for various ailments. The combination of ingredients has anti-inflammatory and analgesic properties. Turmeric contains curcumin, which may inhibit the excessive release of prostaglandins in uterine tissue, reducing uterine contractions. Tamarind has flavonoids with analgesic effects, gotu kola contains triterpenoids that improve blood circulation and relax the uterus, and honey has flavonoids similar to those found in mefenamic acid, providing a natural pain-relief effect. This study aimed to determine the effect of Kuaspadu herbal drink on reducing menstrual pain in female adolescents. This research used a quasi-experimental design with a one-group pre-test and post-test approach. A total of 52 female adolescent participants were involved. Each participant was given 150 ml of Kuaspadu herbal drink every morning after breakfast for three consecutive days during menstruation. The level of menstrual pain was measured before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The statistical analysis showed a significant decrease in menstrual pain after consuming Kuaspadu herbal drink, with a p-value of 0.000 (p < 0.05). This indicates that the herbal drink had a positive effect in reducing menstrual pain among the participants. Kuaspadu herbal drink is effective in reducing menstrual pain in female adolescents and can be considered a natural alternative for managing dysmenorrhea.